2017
DOI: 10.1103/physrevlett.119.144101
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Process Zone and Material Heterogeneities for Dynamic Cracks

Abstract: Using an elastodynamic boundary integral formulation coupled with a cohesive model, we study the problem of a dynamic rupture front propagating along an heterogeneous plane. We show that small-scale heterogeneities facilitate the supershear transition of a mode-II crack. The elastic pulses radiated during front accelerations explain how microscopic variations of fracture toughness change the macroscopic rupture dynamics. Perturbations of dynamic fronts are then systematically studied with different microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…First, we have assumed that slight fluctuation of stress or frictional properties does not significantly affect the overall rupture behavior, which allows for a simplified numerical modeling of laboratory earthquakes. One should bear in mind that this condition may not always be satisfied in laboratory earthquakes, and special care needs to be taken when strongly heterogeneous features emerge (Barras et al, ; Bayart et al, ). Second, we have only modeled one half of symmetrically expanding ruptures to reproduce the major rupture phase of laboratory earthquakes in a selected time window.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have assumed that slight fluctuation of stress or frictional properties does not significantly affect the overall rupture behavior, which allows for a simplified numerical modeling of laboratory earthquakes. One should bear in mind that this condition may not always be satisfied in laboratory earthquakes, and special care needs to be taken when strongly heterogeneous features emerge (Barras et al, ; Bayart et al, ). Second, we have only modeled one half of symmetrically expanding ruptures to reproduce the major rupture phase of laboratory earthquakes in a selected time window.…”
Section: Discussionmentioning
confidence: 99%
“…At t = 0, the crack reaches the critical size L c where G(v = 0, L = L c ) exactly equates the fracture energy G H c and starts to propagate dynamically at a speed v > 0. L c corresponds then to the largest stable crack size [39,43,48] given by where E and ν respectively denote the Young's modulus and Poisson's ratio of the elastic solid, and G H c is the fracture energy of the homogeneous portion of the fracture plane. In an infinite homogeneous solid, Freund [1] showed that the energy release rate evolves with propagation speed as G…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to supersonic aircraft, elastic waves radiated from supershear cracks gather to form shock wave fronts, also referred to as Mach cones, leading to particularly violent earthquakes [32][33][34][35][36]. Several studies have described how local variation in toughness or elastic properties can precisely favor the supershear transition of a mode II crack [37][38][39][40][41][42][43]. Despite the relative rarity of supershear earthquakes reported in nature, recent experiments [44] suggest that shortlived supershear events may frequently occur at small scales of crustal fault, out of the resolution of seismic inversion, yet significantly impacting the rupture dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Later numerical work [10] found that a sufficiently strong shear stress peak can overcome interfacial strength and nucleate a daughter crack that could propagate at supershear velocities. Supershear ruptures have been observed along natural fault planes [34,55], in laboratory experiments [26,85,99,111,127,151,154] and have been extensively investigated by numerical simulations [1,4,20,43,58,65,67,87,88,118]. A further description, however, is beyond the scope of this review.…”
Section: High Amplitude Stress-wave Radiation -Non-singular Contributmentioning
confidence: 99%